A Study of Infrastructure Investment Planning regarding Tourism Development of Sukhothai Historical Park: Alternatives and Socio-Economic Impacts to the Local Communities - Rongwiriyaphanich, Suwanna (Journal of Architectural/Planning Research and Studies (JARS), 2005)
Since 1987, the Thai government has recognized and begun adopting a new approach of development by slowly shifting focus away from a growth orientation approach to a balanced socio-economic development approach as mentioned in the Eighth National Economic and Social Development Plan (1997-2001) aiming to improve the well-being of all people in the Thai society. Though the idea has been limited to development at the regional level at the beginning, the government has latterly realized an importance of development at the local level with respect to the potentials, preferences, and functions of the area. As a case study, this study, therefore, aims to investigate and evaluate socio-economic impacts potentially created to the local communities with regard to the required additional infrastructure investment to support tourism development of Sukhothai Historical Park and the associated historical towns by the two alternatives, i.e. to develop Phitsanulok-the so-called regional-oriented development approach and to develop Sukhothai-the so-called local-oriented development approach, based on development objectives of the present development plans and policies using a scientific method.